PENDAMPINGAN KECAMATAN PENGASIH SEBAGAI KPPE (Penataan Sendangsari Menuju Desa Wisata Alam, Seni, dan Kerajinan Tahap I) - Djawadi, Djawadi (Universitas Negeri Yogyakarta, 2003)
The goal of the public service an the title Assistance of Pengasih Subdistrict Kulon Progo District as the Sendangsari Arrangement to be Tourst Village, Nature, Art and Industry (Part I) are: (1) to know the natural factor and society in Sendangsari Pengasih Kulonprogo that can be developed into ODTW, (2) to know the desire and the ability of the society in Sendangsari Pengasih Kulon Pro go that can support tourism activities.This public service uses sociological-democratic and anthropological approach. The intermediary target object of this public servise are tourism and culture official of Kulon progo District, the subdistric head of Pengasih, the chief and the servant of Sendangsari Village. Mean while, the main target are the famous figures of the Sendangsari Village. The activity method of this public servise are visiting to the Celereng tourist spot, touring area and discussing target object.The result of this public service activity are: 1) The main and intermediary target support the Celereng Tourist Spot Development Programs. 2) There is Kelompok SadarWiscua (Pokdarwis) Sendangsari established based on Keputusan Lurah Desa Sendangsari nomor 04 tahun 2002 tanggal 16 Agustus 2002. 3) The activity programs based on the meeting of the servant team and the target object on August 2, 2002 will be held. The servant team raises some suggestions. They are: 1) The target object should monitor and evaluate the activities regularly and continuously, so the program can be held or the plan. 2) This public service should be continued into part II it can to support the relizaation of Kawasan wisata Clereng that can increase the society welfare around the tourist spot. 3) The intermediary target should increase the coordination with LPM UNY (the servant team), so there is no overlapping program. The programs should support each other depend on its functions.Key words: tourism village